Bis(pyridylimino)isoindolato (BPI) Osmium Complexes: Structural Chemistry and Reactivity - Müller, Astrid; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2015)
A series of osmium complexes with monoanionic, meridionally coordinating 1,3-bis(2-pyridylimino)isoindolates (BPI) as spectator ligands has been synthesized. Reaction of the dichlorido metal precursor [OsCl2(PPh3)3] with the lithiated BPI ligand transfer reagent gave the chlorido complex [(tBu-BPIMe)Os(PPh3)2Cl] (2) which, in turn, was reacted with lithium triethylborohydride to yield the hydrido complex [(tBu-BPIMe)Os(PPh3)2H] (3). Treatment of complex 2 with thallium hexafluorophosphate under a nitrogen pressure afforded the cationic dinitrogen complex [(tBu-BPIMe)Os(PPh3)2(N2)]PF6 (4), which contains an end-on coordinated dinitrogen molecule trans to the isoindolato nitrogen atom. To synthesize the alkynyl complex [(tBu-BPIMe)Os(PPh3)2(C≡CPh)] (5), the chlorido complex 2 was treated with lithium phenylacetylide. Complex 5 was subsequently converted quantitatively by addition of one or two equivalents of HBF4 to the vinylidene complex [(tBu-BPIMe)Os(PPh3)2(═C═CHPh)]BF4 (6), and the cationic species [(H-tBu-BPIMe)Os(PPh3)2(═C═CHPh)](BF4)2 (7), respectively; the latter being formed via protonation of one imine nitrogen atom of the BPI ligand. Upon stirring, a toluene solution of the chlorido complex 2 with benzyl potassium, the four-membered metallacycle [(tBu-BPIMe)Os(PPh3)(o-C6H4PPh2)] (8) was obtained, which reacted with molecular hydrogen and phenyl acetylene to give the hydrido complex 3 and the acetylide complex 5, respectively. Stirring of 8 with methyl acetylenedicarboxylate (DMAD) yielded [(tBu-BPIMe)Os(DMAD)(o-C6H4PPh2)] (9), while treatment with carbon monoxide gave the acyl complex [(tBu-BPIMe)Os(o-C(O)-C6H4PPh2)(CO)] (10) by an insertion of CO into the osmium carbon bond.